2023
DOI: 10.1083/jcb.202308069
|View full text |Cite
|
Sign up to set email alerts
|

Cell polarity changes in cancer initiation and progression

Florent Peglion,
Sandrine Etienne-Manneville

Abstract: Cell polarity, which consists of the morphological, structural, and functional organization of cells along a defined axis, is a feature of healthy cells and tissues. In contrast, abnormal polarity is a hallmark of cancer cells. At the molecular level, key evolutionarily conserved proteins that control polarity establishment and maintenance in various contexts are frequently altered in cancer, but the relevance of these molecular alterations in the oncogenic processes is not always clear. Here, we summarize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Importantly, one needs to bear in mind that the loss of cell polarity is a hallmark of cancer, which does not need to be necessarily linked to HPV presence. Therefore, it is expected that the fluctuations of these PDZ-domain-containing protein expression levels occur in both HPV+ and HPV− tumors [ 44 ]. While this finding might be due to some chance effect in a small population, it was very interesting to note that in the TCGA cohort, the middle-expression group had a worse prognosis than the top- or bottom-expression groups, with the groups starting to diverge noticeably after 30 months of follow-up ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, one needs to bear in mind that the loss of cell polarity is a hallmark of cancer, which does not need to be necessarily linked to HPV presence. Therefore, it is expected that the fluctuations of these PDZ-domain-containing protein expression levels occur in both HPV+ and HPV− tumors [ 44 ]. While this finding might be due to some chance effect in a small population, it was very interesting to note that in the TCGA cohort, the middle-expression group had a worse prognosis than the top- or bottom-expression groups, with the groups starting to diverge noticeably after 30 months of follow-up ( Supplementary Figure S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apicobasal polarity dictates the polarized functioning of epithelial cells, and loss of apicobasal polarity has long been associated with tumor initiation and invasive progression of carcinoma (cancer deriving from epithelial tissues; Macara and McCaffrey, 2013 ; Wodarz and Näthke, 2007 ). Many studies have highlighted that unpolarized epithelia are more prone to carcinoma induction and invasion compared to fully polarized epithelia (reviewed by Lee and Vasioukhin, 2008 ; Peglion and Etienne-Manneville, 2024 ). However, histological analysis of tumor specimens has revealed that invasive cancers like colorectal adenocarcinomas display clearly differentiated morphologies with intact polarized epithelial structures that delineate internal luminal cavities within the neoplastic glands ( Libanje et al, 2019 ).…”
Section: Inverted Polarity In Cancermentioning
confidence: 99%
“…However, histological analysis of tumor specimens has revealed that invasive cancers like colorectal adenocarcinomas display clearly differentiated morphologies with intact polarized epithelial structures that delineate internal luminal cavities within the neoplastic glands ( Libanje et al, 2019 ). Whether the presence of inverted apicobasal polarity in such structures bears consequences for carcinoma pathophysiology is an increasingly explored hypothesis ( Peglion and Etienne-Manneville, 2024 ).…”
Section: Inverted Polarity In Cancermentioning
confidence: 99%
“…17 To fully grasp the complicated functions of cells and their importance in health and illness, it is necessary to understand the way cellular polarity acts. Deviations in the homeostasis of polarity have been associated with a number of hereditary diseases, 18 neurodegenerative conditions for instance Parkinson's and Alzheimer's, 19,20 malignancies, 21 and inflammatory bowel disorders (IBD). 22 In particular, the polarity of cells can affect the uptake, utilization and synthesis of lipids, including polyunsaturated fatty acids (PUFAs), which are key substrates for lipid peroxidation and the initiation of ferroptosis.…”
Section: Introductionmentioning
confidence: 99%